Tax Policy And Economic Growth: A Comparative Analysis Of Different Taxation System (Journal of Namibian Studies : History Politics Culture, 2023)
The tax system in India is crucial to the country's economic growth since it is one of the main ways the government brings in money. Indirect taxes, on the other hand, have an effect on consumer pricing rather than on discretionary income. The primary purpose of this study is to analyse the effects of India's tax policy on the country's GDP. As Indian businesses increasingly compete on a global scale, the country's tax structure is experiencing a dramatic transformation. The Indian government is committed to liberalising the taxes system and eliminating loopholes to prevent evaders from increasing income for the government exchequer and improving the status of business generally. Taxes are an important economic indicator and one of the government's primary income streams. Indirect taxes, on the other hand, have an effect on consumer prices rather than disposable income.